(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The present study investigates the distinctive lexical-semantic characteristics of the modern Uzbek language and critically examines their implementation within the contemporary educational process. Drawing on both quantitative and qualitative linguistic methodologies, the research explores how evolving semantic fields, lexical innovations, and the stratification of vocabulary in Uzbek impact language acquisition, teaching strategies, and the cultivation of linguistic competence among students. The study situates Uzbek within the context of broader Turkic linguistic dynamics, interrogates the interface between traditional lexical heritage and modern neologisms, and scrutinizes the pedagogical implications of semantic change and variation. Key findings indicate that targeted integration of lexical-semantic analysis in curriculum design not only enhances students’ communicative proficiency but also fosters critical cultural and cognitive skills. The paper concludes by recommending systematic, context-sensitive approaches to incorporating lexical-semantic content in language instruction, arguing that such strategies are indispensable for both linguistic and cultural continuity in Uzbekistan’s rapidly modernizing society.